P-141 YI Novel Therapeutic Insights from Mathematical Modeling of Cobblestone Lesion Development in Crohn's Disease. (March 2016) - Rodriguez-Palacios, Alexander; Barbaro, Alethea; Alsenafi, Abdulaziz; Mualem, Judy; Ezeji, Jessica; Cominelli, Fabio
Abstract : Background: Chronic and progressive life-long intestinal inflammation in Crohn's disease (CD) leads to thickening of the gut wall and formation of lesions that protrude into the gut lumen resembling "cobblestones" on a street surface. In addition to the many uncertainties concerning their initiation and propagation, the spatial behavior of such pathognomonic lesions in humans remains uncharacterized because it is impossible to monitor development over time in the same individual. Spontaneous mouse models of CD could be used to assess lesion dynamics. Methods: The objective of this study was to quantify and mathematically model hypothetical mechanisms of lesion progression (initiation and dispersion) in a well-established mouse model of CD, SAMP1/YitFc (SAMP), compared to that of C57BL/6J(B6) TNFdeltaARE/+ (B6 TNFARE ) mice. B6 TNFARE mice have a single gene mutation that leads to overproduction of pro-inflammatory tumor-necrosis-factor (TNF) and enteritis. The genetic cause of inflammation in SAMP is unknown (although it is polygenic based on linkage-analysis and whole-genome-sequencing, as it is CD). We used a lattice-based interacting particle model to simulate the evolution of discrete chronic focal lesions in the small intestine. A rectangular lattice, with each side representing a villous with periodic boundaries in the horizontal direction, recreated a cylindrical lattice. Villous data from CD-free (healthy control) mouse lines C57BL/6J and AKR/J delineated the initializing homogenous tubular gut parameters on the lattice. Three mathematical mechanisms were then explored for the expansion and dissemination of lesions on the lattice. The dimensions of the lesions were lattice represented with experimental stereomicroscopic and histological data obtained from the ilea of CD-affected (3.5, 7, 14 and 30 week-old) mice. Results: Using data from 3-dimensional stereomicroscopic profiling (3D-SMAP gut ) and mathematical modeling, we discovered that the intestinal lesions in the SAMP mouse model uniquely resemble the "cobblestone" lesions typical of CD, and that the lesions in the mouse intestine develop and disperse in a way that remarkably resemble forest fires. The dynamic mechanism of development and expansion in SAMP contrasts the principle and less invasive pattern of B6 TNFARE mice. In B6 TNFARE, lesion development and dispersion is more predictable and symmetric with the resemblance of a growing wave of "villous-aggregation" islands (not cobblestones) that expand from the cecum-ileum junction orally (towards the oral cavity) as animals age. Dynamic visualization of hypothesized dispersion theories on the lattice illustrates cobblestone lesions evolution following prominent principles of forest fire dynamics in SAMP mice. Conclusions: The distinct spatial architecture of the individual lesions in both mouse lines, and their distinct dynamic mechanisms of growth and dispersal indicate that mice affected with progressive intestinal inflammation have distinct conjoint growth-dispersion mechanisms which supports the novel concept that mice of different genetic background may have different conserved pathophysiological mechanisms resulting in unique 3D-inflammatory expansion arrangements in the gut (Rodriguez-Palacios, 2015; doi: 10.1038/ncomms8577). Our findings could help refine theories on therapeutic strategies, determine optimal areas for tissue sampling in immunological studies, and importantly, philosophically envision CD as a disease that has a discrete "burning fire front line" that can be targeted to alleviate disease expansion. Novel therapeutics could be (re)designed keeping in mind such host-genetic-dependent spatial 3D-heterogeneity.